Foliar Versus Soil Application of Nitrogen on Pearl Millet - Kinra, K L; Nijhawan, H L; Rao, S B P (Annals of Arid Zone, 2016)
Foliar application of urea at 11.2 Kg/N and 22 Kg/N per ha prove superior to double these rate of N applied through soil. Nitrogen application increased the protein content of ’bajra’ grain equally by its foliar or double the soil application rate. A corresponding reduction in carbohydrate content was noticed. Fat, crude fibre, total minerals and phosphorus Content of grain remained unaffected. Foliar. application of ’N’ proved more remunerative than its soil application at both levels of N tried.